PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DAN THINK PAIR SHARE PADA MATERI SISTEM KOLOID - Hirma Karmila; Amilda Amilda; Etrie Jayanti (Chemistry Education Department of Education and Teaching Faculty, 2020)
This study aims to (1) find out student’s learning outcomes on colloidal system using Problem Based Learning model; (2) find out student’s learning outcomes on colloidal system material using Think Pair Share learning model; (3) find out how significant difference of student’s learning outcomes between Problem Based Learning and Think Pair Share model. The design used in this study was quasi-experimental of posttest-only control group design. Population of this study was all students of class XI MIA at one of the Private Islamic Senior High School In Palembang. Sampling was conducted through random sampling techniques and then class XI MIA 1 as the experimental class 1 and class XI MIA 2 as the experimental class 2. The instrument used to obtain data was a test consisting of 15 multiple-choice questions. The result shows that the average of students learning outcomes used Problem Based Learning was 72.54 while the average of student’s learning outcomes used Think Pair Share was 68.10. Statistic inferential data gained that tcount 2,384 > ttable 1,992. It can be concluded that H0 is rejected meanwhile H1 is accepted. The data indicates that there is a significant difference between Problem Based Learning and Think Pair Share used on student’s learning outcomes.